Taxes, wages and working hours - Peter Ericson; Lennart Flood (Institute for the Study of Labor (IZA), 2011)
This paper presents estimates of individuals' responses in hourly wages to changes in marginal tax rates. Estimates based on register panel data of Swedish households covering the period 1992 to 2007 produce significant but relatively small net-of-tax rate elasticities. The results vary with family type, with the largest elasticities obtained for single males and the smallest for married/cohabitant females. Despite these seemingly small elasticities, evaluation of the effects of a reduced state tax using a microsimulation model shows that the effort effect matters. The largest effect is due to changes in number of working hours yet including the effort effect results in an almost self-financed reform. As a reference to the earlier literature we also estimate taxable income elasticities. As expected, these are larger than for the hourly wage rates. However, both specifications produce significantly and positive income effects.
urn:nbn:de:101:1-20110927589
Keywords: C8; D31; H24; J22; J31; 330; income taxation; hourly wage rates; work effort; micro simulation; Einkommensteuer; Steuertarif; Elastizität; Lohn; Arbeitsangebot; Arbeitszeit; Schweden